CULTURAL DIVERSITY AND SUSTAINABILITY: TRADITIONAL FISHER FOLK OF KERALA - Josna George C (COGNITIVE DISCOURSES, 2018)
This paper seeks to understand intricacies of traditional fisherfolk. Kerala’s fishing communities shared the ocean’s resources and maintained close social and economic ties despite cultural and religious differences. It is not possible to identify the sector with anyone of the community in Kerala. Fisherfolk provide not only a source of food and work but also a community cultural identity too. Sustainable development maintains that environmental, economic and social issues are interconnected among fisherfolk.